Trauma of the limbs in horses and methods of treatment - Kulynych, S.; Kramarenko, V.; Zezekalo, M. (Scientific Progress & Innovations, 2023)
For the comfortable life of horses, it is important to have healthy hooves, as achieving high sports results requires the distal part of the horseʼs limb to be in proper condition, involving periodic inspections and regular functional orthopedic trimming. Proper care of the limbs and hooves of a horse is a guarantee of its health and well-being. Without the ability to move normally, your hors is at risk of developing various diseases, including traumatic ones. Among the latter, the most common and dangerous is laminitis. The purpose of our work is to conduct monitoring studies on the prevalence of limb injuries in horses and to propose the most optimal treatment schemes for detected pathologies. Monitoring studies were carried out throughout 2022 based on the following facilities: equestrian com-plex "Solomakhino Rancho" in Kyiv; horse farm "KK‒delight" in Bortnichi; horse farm "Rehabilitation center of the club of horse lovers and other animals Hippos" in the Kirovohrad region, Kropyvnytskyi. The spread of limb pathologies in horses was studied using commonly accepted methods and special equipment. The research conducted in the conditions of horse farms and equestrian complexes revealed limb pathologies in animals, including a fracture of the coffin bone of the left pelvic limb, laminitis of the right thoracic limb, chronic laminitis, hoof deformities with signs of partial destruction of the hoof sole horn. The mentioned pathologies were found in animals of different ages during the research. The analysis carried out allowed identifying the most common limb diseases in horses and developing appropriate treatment measures. In particular, for the treatment of horses with acute laminitis, it is rec-ommended to use "Havens" feeds in combination with the local application of clay with added zinc oxide and further fixation with orthopedic shoes and the application of "Magic Cushion" Xtreme EU Hoof Packing material. Addi-tionally, the administration of the drug "Meloxicam" is recommended. In case of chronicization of the pathological process, it is advisable to perform orthopedic trimming with the subsequent use of a bandage with a special mixture consisting of iodine and sugar in a proportion of 1 : 50, which is fixed on the affected limb using a bandage and adhesive-reinforced tape. For fractures of the coffin bone, it is recommended, after mechanical cleaning, to apply a special material, Hoof Care, closer to the heel on the sole area, ensuring the full operation of the hoof mechanism of the affected animal. In the case of detecting deformations in horses, timely trimming is recommended, and when areas of destruction are found, the application of a 10.0 % copper sulfate aerosol on the sole surface of hooves is advised.